An exploration into the quality of life of women treated for cervical cancer - Caroline Sabulei; Johanna E. Maree (AOSIS, 2019)
Background: Cervical cancer mainly occurs among women from the developing world, and women face unique challenges in terms of their disease and treatment. Most women present with advanced cervical cancer and receive the standard curative treatment with external beam radiotherapy and brachytherapy with or without chemotherapy. Objectives: To describe the quality of life (QOL) of women treated for cervical cancer during treatment (M0), at 6 months after completing treatment (M6) and at 12 months after treatment (M12). Methods: A cross-sectional design, calculated sample size (n = 153) and convenience sampling were used. Data were collected through structured interviews, and the EORTC QLQ-C30 and EORTC QLQ CX24 served as data collection instruments. Descriptive statistics were used to analyse the data, and the Kruskal-Wallis H test was used to compare the mean responses across the groups (p ≤ 0.05). Results: The mean age of the respondents was 50.6 years (standard deviation [SD] 11.9). The global health status improved significantly in contrast with the functional scores. Financial difficulties were rampant, especially during the treatment phase. Insomnia and urinary frequency were the most cumbersome problems and remained so even after treatment. Conclusions: Despite an improvement in the global health, cervical cancer and its treatment had a negative influence on the QOL in all domains of lives of these women. Assessing the QOL of patients during treatment and follow-up visits would allow nurses to develop interventions to address distressing problems timeously. In addition, Africa's nurses should assess social functioning and develop programmes to prevent social dysfunction.